Sistem Informasi E-Learning Pada Sekolah Dasar Islam Nailufar Jakarta - Amelianda Mega Putri; Syifa Nur Rakhmah (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
The learning system of the Nailufar Islamic Elementary School is currently carried out using face-to-face learning methods, zoom applications, whatsapp and Microsoft Excel in processing grades, thus allowing for lost or damaged test papers and errors when inputting student grades which cause the data to be inaccurate. In developing an information system, researchers use the application of User Center Design, where researchers conduct observations and interviews with the school to determine the system requirements in the development of this e-learning system. The e-learning system that the researcher proposes can store teacher data, student data, view lesson schedules, read material, make assignments or exam questions, upload assignments, take exams and display print results from student scores. With this system, it can facilitate the implementation of teaching and learning activities and the making of student grade reports. This e-learning system that has been designed can also avoid lost or damaged documents so that the learning system used by the Nailufar Islamic Elementary School becomes more effective, efficient and the resulting data is more accurate. Keywords: Design, E-Learning, User Center Design Abstrak Sistem pembelajaran Sekolah Dasar Islam Nailufar saat ini dilakukan dengan metode pembelajaran tatap muka, aplikasi zoom, whatsapp maupun Microsoft Excel pada pengolahan nilainya, sehingga memungkinkan hilang atau rusaknya kertas ujian dan kesalahan pada saat menginput nilai siswa yang menyebabkan data menjadi tidak akurat. Pada pengembangan sistem informasi peneliti menggunakan penerapan User Center Design, dimana peneliti melakukan observasi dan wawancara kepada pihak sekolah untuk mengetahui kebutuhan sistem dalam pembangunan sistem e-learning ini. Sistem e-learning yang peneliti usulkan ini dapat menyimpan data guru, data siswa, melihat jadwal pelajaran, membaca materi, membuat soal tugas atau ujian, mengupload tugas, mengerjakan ujian serta menampilkan hasil print dari nilai siswa. Dengan adanya sistem tersebut dapat mempermudah pelaksanaan kegiatan belajar mengajar dan pembuatan laporan nilai siswa. Sistem e-learning yang telah dirancang ini juga dapat menghindari hilang atau rusaknya dokumen sehingga sistem pembelajaran yang digunakan Sekolah Dasar Islam Nailufar menjadi lebih efektif, efisien dan data yang dihasilkan lebih akurat. Kata kunci: Desain, E-Learning, User Center Design